What is the best way to train to become a star endurance athlete? - Stöggl, T. L. (Frontiers for Young Minds, 2018)
This article deals with the best way to train to maximize performance in endurance sports. Most scientific studies show that successful endurance athletes use a training concept with a great proportion of training with low exercise intensity (Zone 1—e.g., running with low to moderate speed over longer time) combined with training sessions using very high exercise intensities (Zone 3—e.g., interval training, repeated sprints) and almost no training in the moderate-intensity zone (Zone 2). This is called polarized training. Athletes generally start their training year with a Zone 1-oriented training concept. In the months before the first competitions start, they switch to a training concept with high proportion of Zone 1, and an increased amount of Zone 2 and Zone 3 training. Within the competition phase, they generally use polarized training. The article will also discuss the problems scientists face when studying how elite endurance athletes train and will introduce some questions that still do not have solid answers.